P-113 YI Body Fat and Skeletal Muscle Composition Differs in Crohn's Disease Patients Depending on Radiological Response to Medical Therapy. (March 2016) - Deepak, Parakkal; Takahashi, Naoki; Fidler, Jeff; Barlow, John; Kolbe, Amy; Loftus, Edward; Bruining, David; Moynagh, Michael
Abstract : Background: Prior studies have demonstrated changes in body fat composition after initiation of infliximab therapy. Radiological transmural response to medical therapies has recently been shown to be associated with better long-term outcomes in small bowel Crohn's disease (CD). We sought to explore changes in body fat and skeletal muscle composition as surrogate biomarkers of radiological response after treatment initiation. Methods: We conducted a pilot study on patients with small bowel CD who underwent a computed tomography enterography (CTE) prior to initiation of therapy with follow-up CTE after median 447 days (IQR, 369–629 days). Small bowel lesions were scored for length, enhancement, mural thickness, dilated vasa recta, perienteric inflammation, penetrating or stricturing disease. Patients were complete responders if all lesions improved, non-responders if existing lesion(s) worsened or new lesion detected, and partial responders for other scenarios. The total cross-sectional area of subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), intramuscular adipose free tissue (IMAFT) and intermuscular adipose tissue (IMAT) were measured at the mid-vertebral level over contiguous axial CT images from the first lumbar (L1) to the third sacral (S3) vertebrae and subsequently summated to give a volumetric analysis. A representative axial image at each level was identified by a single radiologist (MM), with images subsequently undergoing semiautomated analysis using in-house developed image processing algorithms (NT, MATLAB 13.0; Math Works, Natick, MA). To calculate SAT and VAT area (cm 2 ), the outer and inner boundaries of the abdominal wall and paraspinal muscles were demarcated. Adipose cross-sectional area was calculated by applying a CT threshold attenuation value between −190 and −30 Hounsfield Units (HU). Lean skeletal muscle (IMAFT) was measured using threshold attenuation values between −29 to +150 HU. Right lower quadrant (RLQ) VAT was selected encompassing the right half VAT between L4 to S3 levels. Both VAT and RLQ VAT were standardized for height by dividing by height-squared. Body adipose composition at baseline and change at 1st follow up CTE ("delta") of complete/partial responders and non-responders were compared using Wilcoxon rank-sum test. Results: A total of 20 CD patients were included: 10 complete responders (50%), 4 partial responders (20%), and 6 non-responders (30%). At baseline CTE, standardized VAT (264.8 [IQR, 171.8–407.2] versus 203.6 [75.1–356.9]), standardized RLQ VAT (56.6 [25.2–78.2] versus 39.2 [15.9–75.2]) and IMAFT (1070.6 [851.9–1491.9] versus 1055.7 [927.1–1423.1]) were similar between radiological responders and non-responders, respectively. After treatment initiation, the standardized delta VAT was similar between the 2 groups while the standardized delta RLQ VAT (5.4 [−6.3 to 19.2] versus −2.4 [−14.7 to 0.1], P = 0.08) showed a trend towards significance. Delta IMAFT (54.1 [1.7–109.1] versus—72.3 [−114.8 to 17.2], P = 0.009) was significantly different between radiological responders and nonresponders. Conclusions: The change in RLQ VAT and IMAFT after initiation of medical therapy potentially differs among radiological responders versus non-responders. These findings suggest a role for analysis of body fat and skeletal composition as a surrogate biomarker for radiological response.